Alcohol use among a community‐based sample of gay men: Correlates of high‐risk use and implications for service provision. (29th December 2014) - Lea, Toby; Ryan, Dermot; Prestage, Garrett; Zablotska, Iryna; Mao, Limin; de Wit, John; Holt, Martin
Abstract Introduction and Aims International research has shown that gay, bisexual and other homosexually active men (hereafter 'gay men') report disproportionately higher rates of risky alcohol use and associated problems compared with heterosexual men. However, little is known about alcohol use among this population in Australia. This study aimed to examine rates of risky alcohol use among a community‐based sample of gay men in Sydney and characteristics of men reporting high‐risk alcohol use and adverse consequences. Design and Methods A cross‐sectional survey of gay men was conducted in Sydney in August 2013 as part of the ongoing Gay Community Periodic Surveys (n = 1546 eligible respondents). The Alcohol Use Disorders Identification Test–Consumption questions were used to assess alcohol use in the previous 12 months. Results Nine percent of respondents were categorised as abstinent from alcohol, 33% as low‐risk drinkers, 42% as moderate‐risk drinkers and 16% as high‐risk drinkers. In separate multivariate logistic regression analyses, high‐risk drinking and reporting ≥4 adverse alcohol consequences were associated with younger age, being Australian‐born, recruitment from licensed premises and having met men for sex at gay bars and dance parties. Fifty‐eight percent of high‐risk drinkers reported a desire to reduce their alcohol use. Discussion and Conclusions In this community‐based sample of gay men, we found high levels of moderate‐ to high‐risk alcohol use. The results suggest that gay men should be a priority population for health promotion campaigns and treatment services. [Lea T, Ryan D, Prestage G, Zablotska I, Mao L, de Wit J, Holt M. Alcohol use among a community‐based sample of gay men: Correlates of high‐risk use and implications for service provision. Drug Alcohol Rev 2015;34:349–357]